2017
DOI: 10.1128/aac.00207-17
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Model Linking Plasma and Peripheral Blood Mononuclear Cell Concentrations of Efavirenz and Its Metabolite, 8-Hydroxy-Efavirenz, in HIV Patients

Abstract: The objectives of this study were to characterize the population pharmacokinetics (PK) of efavirenz (EFV) and 8-hydroxy-efavirenz (8OHEFV) in plasma and peripheral blood mononuclear cells (PBMCs) and to explore covariates affecting the PK parameters. Fifty-one patients had steady-state 0-to-24-h concentrations of EFV and 8OHEFV in plasma with corresponding concentrations in PBMCs, while 261 patients had one or two sparse concentrations at 16 Ϯ 1 h postdose at weeks 4 and/or 16. The pharmacogenetic markers CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Furthermore, the finding indicates that the impact of CYP2B6*6 on EFV PKs is higher in children compared to adult Ethiopians, as Habtwolde et al estimated, about two-fold lower EFV CL for adults with CYP2B6*6/*6. 37 Second, consistent with previous studies in adult subjects, 11,22,23 this study finds that ABCB1 c.4036A>G (rs3842) genetic polymorphism has a significant impact on EFV PKs, a finding which to our knowledge has not been reported previously in pediatric subjects. Third, consistent with results from previous pediatric and adult studies, 5,6,15 this study demonstrates EFV autoinduction phenomenon in pediatric subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the finding indicates that the impact of CYP2B6*6 on EFV PKs is higher in children compared to adult Ethiopians, as Habtwolde et al estimated, about two-fold lower EFV CL for adults with CYP2B6*6/*6. 37 Second, consistent with previous studies in adult subjects, 11,22,23 this study finds that ABCB1 c.4036A>G (rs3842) genetic polymorphism has a significant impact on EFV PKs, a finding which to our knowledge has not been reported previously in pediatric subjects. Third, consistent with results from previous pediatric and adult studies, 5,6,15 this study demonstrates EFV autoinduction phenomenon in pediatric subjects.…”
Section: Discussionsupporting
confidence: 91%
“…The determination of plasma efavirenz by LC‐MS/MS was performed as described previously (Burhenne et al, 2010 ; Habtewold et al, 2016 ; Habtewold et al, 2017 ). The method was validated according to the FDA validation guidelines and fulfilled all criteria concerning accuracy, precision, recovery, linearity, and stability.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction dynamics describing HIV infection are adapted directly from the basic HIV model (Ho et al, 1995 ; Wei et al, 1995 ; Perelson et al, 1997 ; Nowak and May, 2000 ; Perelson and Ribeiro, 2013 ). Published pharmacokinetic studies have been used for modeling the dynamics of anti-retroviral drugs in both plasma and lymphoid lobule (Dixit and Perelson, 2004 ; Hurwitz et al, 2007 ; Arab-Alameddine et al, 2012 ; Habtewold et al, 2017 ). Modeling assumptions concerning transport of T cells and antiretroviral drugs are as follows:…”
Section: Biological Backgroundmentioning
confidence: 99%
“…Currently five different NNRTIs have been approved by FDA for antiretroviral therapy. For our current study we chose to use efarivenz due to the availability of a previously published intracellular pharmacokinetic model by Habtewold et al ( 2017 ) as shown in Figure 5 . Efarivenz (EFV) is usually prescribed once daily in doses of 600mg single pill.…”
Section: Biological Backgroundmentioning
confidence: 99%